Sir William Osler, eugenics, racism, and the Komagata Maru incident. Issue 1 (2nd January 2021) - Bryan, Charles S.
Abstract: A recent critic levels two new charges against Sir William Osler: (1) that in 1912 he was a vice president of the First International Eugenics Congress; and (2) that in 1914 he asserted Canada should remain a "a white man's country." Osler was indeed among the 31 vice presidents of the First International Eugenics Congress, but he did nothing further in this area. Osler indeed asserted that Canada should remain a "white man's country, " but his context was the Komagata Maru incident during which most Canadians felt the same way about 376 passengers from the Punjab Province of British India who sought to defy Canadian immigration law. There is little or no indication of racism elsewhere in Osler's deeds and writings, and the idea that race is largely a social construct emerged only after his death. Advocates for racial equality should view Osler not as an adversary but rather as an ally in today's battles for global justice and also for human survival.